Are Conventional Learning media Still Effective in the 21st Century? : A Case Study of PAK Teachers at Kononia Sentani Christian High School, Jayapura Regency - Talo, Amsi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This study examines the effectiveness of conventional learning media in the 21st century in teaching Christian Religious Education (PAK) at Kononia Sentani Christian High School, Jayapura Regency. This study uses a qualitative method with a case study approach to explore the implementation of conventional learning media in Christian Religious Education in the midst of rapid digital technology development. The subjects of the study consisted of two teachers of Christian Religious Education and twenty grade IX students who were actively involved in teaching and learning activities. Data was collected through observation techniques, structured interviews, and documentation. Observation assesses students' creativity, enthusiasm for participating in lessons, and active involvement in class. The structured interview delves into the use of conventional media in the context of 21st-century learning. Documentation includes analysis of the Learning Implementation Plan, student projects, and other supporting documents. The data was analyzed through transcription, interview reduction, and integration of observation results and documents, followed by verification to conclude. The findings of the study show that PAK teachers at Kononia High School use conventional media to support learning activities in the classroom and identify challenges in the application of modern learning media and recommend increasing pedagogical competence and technology integration to meet the demands of contemporary education.